The effect of civil unrest on nursing personnel and nursing services in the Cape Peninsula during 1986 - Clow, Sheila Elizabeth (Division of Nursing and Midwifery, 2023)
Civil unrest has become a feature of South African society and has resulted in varying degrees of social disruption. Health services, particularly those located in residential areas, have been affected. As nurses constitute the largest group of health care professionals in South Africa, and often live in the communities in which they work, they serve as useful indicators both of community dynamics and the health services. This study describes the effect of civil unrest on nursing personnel and determines the short term and long term effects on health and nursing services. A self-administered questionnaire was distributed to all community based nurses working in two major health services in the Cape Peninsula in 1986. In addition, routinely available health data directly related to nursing services were collected on a monthly basis for the period 1984-1988 (inclusive). For purpose of analysis the Cape Peninsula was classified into areas of high, medium and low impact violence evident in 1986. The nursing questionnaire had a response rate of 76.9%. Problems associated with civil violence that were identified were the need for nurses to ensure the safety of their own children; transportation to and from work; identification as nurses; security; curtailment of nursing services (particularly home visits); disruption of ancillary services; employer attitudes; political and police activity. Health data relating directly to nursing services revealed disrupted antenatal dinics, an increase in the number of women booking antenatally following a time of disrupted booking clinics, an increase in deliveries associated with interrupted family planning clinics, a decrease in treatment of ophthalmia neonatorum and umbilical sepsis associated with curtailed home visits. The study indicated that nurses wer:a not adequately equipped to cope with the changing demands mad1:1 upon them during periods of political instability; that civil unrest negatively affects nursing personnel and nursing services; and further, that disruption of a service impacted other services. It is recommended that in areas of violence it is essential to have a single management team co-ordinating all health services; education and in-service training must address the needs of nurses.and health care in situations of civil violence; nurses must strive to be accepted as universal carers and be committed to justice and peace; and the professional association must be proactive in providing guidelines to nurses who are affected by civil unrest.